Ethanol extracts of Scutellaria baicalensisprotect against lipopolysaccharide-induced acute liver injury in mice - Nguyen, Thanh Hai (Elsevier, 2016)
Objective: To investigated the protective potential of ethanol extracts of Scutellaria baicalensis (S. baicalensis) against lipopolysaccharide (LPS)-induced liver injury. Methods:Dried roots of S. baicalensiswere extracted with ethanol and concentrated to yield a dry residue. Mice were administered 200 mg/kg of the ethanol extracts orally once daily for one week. Animals were subsequently administered a single dose of LPS(5 mg/kg of body weight, intraperitoneal injection). Both protein and mRNAlevels of cytokines, such as tumor necrosis factor alpha, interleukin-1β, and interleukin-6 in liver tissues were evaluated by ELISA assay and quantitative PCR. Cyclooxygenase-2, inducible nitric oxide synthase, and nuclear factor-κB protein levels in liver tissues were analyzed by western blotting. Results:Liver injury induced by LPSsignificantly increased necrosis factor alpha, interleukin-1β, interleukin-6, cyclooxygenase-2, inducible nitric oxide synthase, and nuclear factor-κB in liver tissues. Treatment with ethanol extracts of S. baicalensisprevented all of these observed changes associated with LPS-induced injury in liver mice. Conclusions:Our study showed that S. baicalensisis potentially protective against LPS-induced liver injury in mice